2017
DOI: 10.3892/mmr.2017.6570
|View full text |Cite
|
Sign up to set email alerts
|

Effects of unfractionated heparin and rivaroxaban on the expression of heparanase and fibroblast growth factor 2 in human osteoblasts

Abstract: Long-term treatment with anticoagulants may contribute to osteoporosis. Although unfractionated heparin and rivaroxaban have adverse effects on bone microstructure and function in adult rats, the underlying mechanism remains to be elucidated. Heparanase (HPSE) and fibroblast growth factor (FGF)2 are important signals in bone formation and fracture healing. Therefore, the present study was designed to investigate the effects of unfractionated heparin and rivaroxaban on the expression of HPSE and FGF2 in human o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…It has been reported that the expression of growth factors such as VEGF, HGF, bFGF, FGF-2, and transforming growth factor-β/β1 which play essential roles in EMT, bone formation, angiogenesis, tumor angiogenesis, and renal diseases, are regulated by heparanase. This effect of heparanase is observed in both in vivo and in vitro studies and is through either its enzymatic or non-enzymatic activities [76,168,[175][176][177][178][179][180][181].…”
Section: Heparanase Regulates Gene and Protein Expression And Protein Activationmentioning
confidence: 99%
“…It has been reported that the expression of growth factors such as VEGF, HGF, bFGF, FGF-2, and transforming growth factor-β/β1 which play essential roles in EMT, bone formation, angiogenesis, tumor angiogenesis, and renal diseases, are regulated by heparanase. This effect of heparanase is observed in both in vivo and in vitro studies and is through either its enzymatic or non-enzymatic activities [76,168,[175][176][177][178][179][180][181].…”
Section: Heparanase Regulates Gene and Protein Expression And Protein Activationmentioning
confidence: 99%
“…Indeed, recent studies have shown that bFGF increases osteoclast activity in vitro and that this increasing activity is inhibited by FGFR3-deficient osteoclasts, which revealed the directly positive effect of bFGF-FGFR3 signaling on osteoclast regulation 45 . However, bFGF signaling is also known to affect osteoblast activity 46 . bFGF is expressed in osteoblasts and induces osteogenesis in a stage-specific manner in osteoblastic cells 47 .…”
Section: Discussionmentioning
confidence: 99%
“…Long-term treatment with glucocorticoids can lead to decreased intestinal calcium absorption, increased urinary calcium excretion, and increased serum thyroid hormones, leading to bone loss [ 13 , 14 ]. Prolonged use of drugs such as proton-pump inhibitors [ 15 ], antiepileptic drugs [ 16 ], diuretics [ 17 ], anticoagulants [ 18 ], and cyclosporine A [ 19 ] can cause severe bone loss. In addition to diseases and drug use, poor living habits, such as alcoholism, smoking, low physical activity, and long-term lack of vitamin intake, can lead to bone loss, which can in turn cause secondary osteoporosis [ 20 ].…”
Section: Introductionmentioning
confidence: 99%